Allele‐specific expression of the serotonin transporter and its transcription factors following lamotrigine treatment in vitro1. Issue 5 (14th June 2013) - D'Souza, Ursula M.; Powell‐Smith, Georgia; Haddley, Kate; Powell, Timothy R.; Bubb, Vivien J.; Price, Tom; McGuffin, Peter; Quinn, John P.; Farmer, Anne E.
Abstract Lamotrigine, a mood stabilizer used clinically in the treatment of bipolar disorder, is thought to exert actions on the serotonin system. However lamotrigine's exact mechanism of action remains unclear. The current study investigated whether lamotrigine might exert its effects through altering the expression of the serotonin transporter (5‐HTT) gene and its regulatory transcription factors Y box binding protein 1 (YB‐1) and CCCTC‐binding factor (CTCF). We further considered whether functional variable number tandem repeat (VNTR) polymorphisms in the promoter region of 5‐HTT, (5‐HTTLPR) and within intron 2 (Stin2) of the gene, moderated any putative gene expression changes. The study employed an in vitro design carried out in human lymphoblastoid cell lines (LCLs) to investigate the effects of lamotrigine treatment at 0.04, 0.2, and 0.4 mM doses for 24 hr on the mRNA expression of 5‐HTT, YB‐1, and CTCF. LCLs were selected based on combinations of haplotypes of the two VNTRs in the serotonin transporter gene; creating low‐expressing and high‐expressing LCL groups. Ubiquitin C (UBC) and topoisomerase I (TOP1) genes were found to be the most stably expressed housekeeping genes in drug‐treated LCLs. Subsequently, quantitative PCR revealed that higher doses of lamotrigine significantly lowered 5‐HTT expression and increased CTCF expression. Haplotype‐specific differences in CTCF expression were found in response to lamotrigine, with strongest expression changes observed in the high‐expressing LCLs. These data provide an allele‐specific in vitro model for examining the molecular targets of lamotrigine, and support the important role of the serotonin transporter gene in its clinical mechanism of action. © 2013 Wiley Periodicals, Inc.